Nomina nova in Platyhelminthes pro Macrorhynchus von Graff, 1882 (non [Gmelin, 1801]; non Dunker, 1843), and Leptocleidus Mueller, 1936 (non Andrews, 1922) - Hornung, J. J. (Zootaxa, 2016)
Two genus-group names of flat-worms—Leptocleidus Mueller, 1936 and Macrorhynchus von Graff, 1882—are junior homonyms that are preoccupied by fossil diapsid reptile genera—Leptocleidus Andrews, 1922, and Macrorhynchus Dunker, 1843—and an extant teleost fish genus—Macrorhynchus [Gmelin, 1801] ex La Cépède, 1800. These are replaced by nomina nova (Pharyngodytes nom. nov.; Graffiellus nom. nov.). Macrorhynchus [Gmelin, 1801] is an objective senior synonym of Macrorhyncus Dumeríl, 1805 ex La Cépède, 1800 (syn. nov.), and a senior homonym of Macrorhynchus Dunker, 1843, and Macrorhynchus von Graff, 1882.